Maintenance of Labor Resources as Fundamentals of Sustainable Manufacturing Development - Danova, Karyna; Malysheva, Viktoriia; Rosokha, Volodymyr; Glushenkova, Irina; Popovych, Nataliia (European Journal of Sustainable Development, 2020)
It is impossible to ensure sustainable business development without solving the maintenance of labor resources issues that are included in the manufacturing process, as well as involving new employees to increase labor potential. The company can effectively confront the new challenges by attracting highly qualified employees for whom a high level of safety is important. Therefore, an important direction of sustainable business development is to increase the level of safety and create a comfortable working environment and optimize working processes to increase the efficiency of production activities, as well as prepare for the challenges that may arise in the process of company development. The article analyzes the statistics and structure of the socio-economic damage to business due to unsatisfactory working conditions and a high level of injuries on the example of the machine-building sector, and also considers aspects of maintenance of labor resources and ways to involve additional labor resources to ensure sustainable manufacturing development. Based on conducted analysis, an algorithm of implementation of managerial decisions was developed, aimed at ensuring the safety of personnel who carry out the work activities at the workplace, taking into account the modern concept of the “green workplace”. Involvement in the working process of additional labor reserves is carried out by creating favorable working conditions, assessing the special needs and level of ability of workers for optimization of working processes and increasing their efficiency. Keywords: Labor Resources, Sustainable Development, Safety, Disability.